2018
DOI: 10.3390/molecules23051200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Insecticidal Constituents from the Essential Oil from the Aerial Parts Stachys riederi var. japonica

Abstract: The essential oil of Stachys riederi var. japonica (Family: Lamiaceae) was extracted by hydrodistillation and determined by GC and GC-MS. A total of 40 components were identified, representing 96.01% of the total oil composition. The major compounds in the essential oil were acetanisole (15.43%), anisole (9.43%), 1,8-cineole (8.07%), geraniol (7.89%), eugenol (4.54%), caryophyllene oxide (4.47%), caryophyllene (4.21%) and linalool (4.07%). Five active constituents (acetanisole, anisole, 1,8-cineole, eugenol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…They occur as secondary metabolism products in several plant groups and play an important protective role against several pathogens, such as bacteria, fungi, and insects (Bakkali et al 2008;Gols 2014). The EOs may act as contact insecticides or fumigant as well as behavior-modifier (attractancy or repellency) in many pest insects (Miresmailli and Isman 2014;Raut and Karuppayil 2014;Quan et al 2018), constituting an effective alternative to synthetic pesticides without producing adverse effects on humans and the environment (Isman and Machial 2006;Regnault-Roger et al 2012). Today, the researches have focused on the search of repellent substances (Nerio et al 2010), where Eucalyptus globulus (Labill) and Foeniculum vulgare Mill.…”
Section: Introductionmentioning
confidence: 99%
“…They occur as secondary metabolism products in several plant groups and play an important protective role against several pathogens, such as bacteria, fungi, and insects (Bakkali et al 2008;Gols 2014). The EOs may act as contact insecticides or fumigant as well as behavior-modifier (attractancy or repellency) in many pest insects (Miresmailli and Isman 2014;Raut and Karuppayil 2014;Quan et al 2018), constituting an effective alternative to synthetic pesticides without producing adverse effects on humans and the environment (Isman and Machial 2006;Regnault-Roger et al 2012). Today, the researches have focused on the search of repellent substances (Nerio et al 2010), where Eucalyptus globulus (Labill) and Foeniculum vulgare Mill.…”
Section: Introductionmentioning
confidence: 99%
“…The essential oil was 373 times less toxic against the booklice than dichlorvos. However, comparison with published fumigant toxicity data for other essential oils using the same assay revealed that they were less toxic against the booklice than the essential oil from the aerial parts of S. baicalensis [17][18][19]. Moreover, the oil was less toxic than the essential oils from A. chinense [20].…”
Section: Discussionmentioning
confidence: 87%
“…The vapor-liquid equilibrium in the system acetic acid + anisole was recently studied by Mali, Mali, Patil, and Joshi (2017). The anisole exhibits insecticide properties and has been studied in recent years (Quan, Liu, and Liu, 2018). Platt (2016) discussed the performance of two stochastic algorithms in the azeotrope calculations, yet employing a different approach to the used in this work, mainly regarding the strategies used to obtain multiple solutions.…”
Section: Introductionmentioning
confidence: 99%